Age and productivity as determinants of firm survival over the industry life cycle. Issue 2 (7th February 2018) - Esteve-Pérez, Silviano; Pieri, Fabio; Rodriguez, Diego
Abstract: This paper contributes to fill the gap between the literature on the determinants of firm survival and the empirical works on the industry life cycle (ILC). Using a representative sample of Spanish firms with 10 or more employees over the period 1993–2009, the role played by firm age and productivity in firm survival is empirically analysed across three stages of the life cycle of forty-seven 3-digit manufacturing sectors. In the 'early' stage of the ILC, firm age is negatively correlated with hazard rates while firm productivity is not. Firm productivity is associated with lower hazard in the 'mature' stage of the ILC, when competition is primarily efficiency-driven, while firm age does not play a significant role for firm survival. In the 'intermediate' stage, both age and productivity play a role in reducing firms' hazard rates.